2003
DOI: 10.1002/hed.10217
|View full text |Cite
|
Sign up to set email alerts
|

Health profiles and quality of life of 518 survivors of thyroid cancer

Abstract: Thyroid cancer survivors generally report good health long term but describe distinct, lasting medical problems including symptoms of thyroid dysregulation. The extent and manner in which cancer therapy contributes to the health profile of the group merits further inquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 18 publications
5
81
1
4
Order By: Relevance
“…On analyzing 518 replies from thyroid cancer survivors from among 7000 surveys mailed to subjects who had been diagnosed with cancer, Schultz et al (2003) found that DTC survivors more frequently reported that their cancer had effected their overall health than did survivors of any other cancer type; fairly severe psychological problems, memory loss, and migraine were recorded. In our pilot study (Giusti et al, 2005) in which QoL was evaluated in 61 DTC subjects by means of a semi-structured interview, HAM-D and KSQ, we found a greater perception of illness among DTC subjects than among 64 control subjects with a history of thyroidectomy for nonmalignant thyroid pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On analyzing 518 replies from thyroid cancer survivors from among 7000 surveys mailed to subjects who had been diagnosed with cancer, Schultz et al (2003) found that DTC survivors more frequently reported that their cancer had effected their overall health than did survivors of any other cancer type; fairly severe psychological problems, memory loss, and migraine were recorded. In our pilot study (Giusti et al, 2005) in which QoL was evaluated in 61 DTC subjects by means of a semi-structured interview, HAM-D and KSQ, we found a greater perception of illness among DTC subjects than among 64 control subjects with a history of thyroidectomy for nonmalignant thyroid pathology.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, few studies have evaluated QoL in DTC subjects on stabilized levo-thyroxine (L-T4) suppressive treatment a long time after primary therapies. Moreover, these studies have been hampered by the small number of subjects involved and of QoL questionnaires administered and by the type of control group chosen (Crevenna et al, 2003;Schultz et al, 2003;Dagan et al, 2004;Tan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, various studies have reported a link between reduced HRQL and DTC (8,21,33,34). HRQL is now considered an important endpoint in clincial studies (35).…”
Section: Dtc-h (%)mentioning
confidence: 99%
“…Most studies on thyroid cancer survivorship in North America have reported a modest decrease in quality of life (QoL) after treatment (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, careful review of these data shows that the study populations were small, the tools were inconsistent and not tailored for thyroid cancer survivors, the sampling techniques did not take into account the varied survivor populations found in modern society, and only five small studies were conducted in the United States (12,14,16,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…However, careful review of these data shows that the study populations were small, the tools were inconsistent and not tailored for thyroid cancer survivors, the sampling techniques did not take into account the varied survivor populations found in modern society, and only five small studies were conducted in the United States (12,14,16,18,19). Without improved information on thyroid cancer QoL outcomes, it will not be possible to develop monitoring tools, intervention strategies, and thyroid cancer-specific survivorship care plans that are relevant to survivor needs.…”
Section: Introductionmentioning
confidence: 99%